Periprocedural, early, and long-term risks of pacemaker implantation after atrioventricular nodal re-entry tachycardia ablation: a French nationwide cohort. Issue 10 (12th August 2020) - Decroocq, Marie; Rousselet, Louis; Riant, Margaux; Norberciak, Laurène; Viart, Guillaume; Guyomar, Yves; Graux, Pierre; Maréchaux, Sylvestre; Germain, Marysa; Menet, Aymeric
Abstract: Aims: Pacemaker implantation (PI) after atrioventricular nodal re-entry tachycardia (AVNRT) ablation is a dreadful complication. We aimed to assess periprocedural, early, and late risks for PI. Methods and results: All 27 022 patients who underwent latest AVNRT ablation in France from 2009 to 2017, were identified in the nationwide medicalization database. A control group of 305 152 patients hospitalized for arm, leg, or skin injuries with no history of AVNRT or supraventricular tachycardia were selected. After propensity score matching, both groups had mean age of 53 ± 18 years and were predominantly female (64%). During this 9-year period, 822 of 27 022 (3.0%) AVNRT patients underwent PI, with significant higher risk in propensity-matched AVNRT patients compared to propensity-matched controls [2.9% vs. 0.9%; hazard ratio 3.4 (2.9–3.9), P  < 0.0001]. This excess risk was significant during all follow-up, including periprocedural (1st month), early (1–6 months), and late (>6 months) risk periods. Annualized late risk per 100 AVNRT patients was 0.2%. In comparison to controls, excess risk was 0.2% in <30-year-old AVNRT patients; 0.7% in 30–50-year-old; 1.1% in 50–70-year-old and 6.5% over 70-year-olds. Risk for PI was also significantly different according to three procedural factors: centres, experience, and ablation date, with a 30% decrease since 2015. Conclusion: Periprocedural, early, and late risks for PI were higher after AVNRT ablation compared to propensity-matched controls. Longer follow-up is needed as the excess risk seems to persist late after AVNRT ablation.